Experimental study on double-headed screw joints and their application in bamboo shear walls. Issue 5 (April 2021) - Lv, Qingfang; Ding, Yi; Liu, Ye
Due to the weak withdrawal capacities of conventional nail joints, using double-headed screw joints as reliable connections in bamboo structures is investigated for the first time. A two-step test program is presented in this paper. In the first step, a double shear test is carried out to investigate the influences of the end distance and bamboo grain direction on the performance of double-headed screw joints. The test shows that there are four main failure modes of double-headed screw joints: double-headed screw shear failure, bearing failure of the hole wall, tensile failure of the bamboo cover panel and shear failure of the cover panel end. In the second step of test, the proposed double-headed screw joints are applied to three single-layer single-span bamboo shear walls, and low-cycle reversed loading tests are applied to the walls with double-headed screw spacings of 50 mm, 100 mm and 150 mm. The failure mode, hysteretic behaviour and energy dissipation performance of the shear walls are discussed. Test results show that the two main failure modes of the bamboo shear walls are the tensile failure of the edge of the wall and shear failure of the double-headed screws. Among the different spacings, the bearing capacity and effective stiffness of the wall with a double-headed screw spacing of 50 mm are the largest, the ductility and energy dissipation capacity of the bamboo shear wall with a double-headed screw spacing of 100 mm are the largest, and the bearing capacity and ductility of the bamboo shear wall with a double-headed screw spacing of 150 mm are the worst.